Patterns of alcohol intake of pregnant and lactating women in Perth, Australia - Giglia, Roslyn; Binns, Colin (Taylor and Francis, 2007)
Introduction and Aims. Australian alcohol consumption data for women during the period of pregnancy and lactation is limited. The purpose of this paper is to provide current alcohol consumption data for pregnant and lactating women in Perth, Western Australia (WA). Data were collected from 587 women between mid-September 2002 and mid-July 2003. Design and Methods. Women from two public hospitals with maternity wards in the Perth metropolitan area completed a self-administered baseline questionnaire while in hospital or shortly after discharge. All women, regardless of their chosen infant feeding method, were followed-up by telephone interview at 4, 10, 16, 22, 32, 40 and 52 weeks postpartum. Data were analysed to determine alcohol use patterns of the women during the period of pregnancy and lactation and results were compared to national guidelines for alcohol consumption.Results. Approximately 32% of women stopped drinking alcohol during pregnancy. A remaining 35% of pregnant women consumed alcohol during pregnancy, with 82.2% of these women consuming up to two standard drinks per week. At 4, 6 and 12 months postpartum, 46.7%, 47.4% and 42.3% of breastfeeding women were consuming alcohol, respectively. Discussion and Conclusions. The majority of breastfeeding women consumed up to two standard drinks per week, which is within levels recommended by national authorities. There is, however, a small proportion of women consuming alcohol at levels above national recommendations for pregnancy and lactation. The development of ‘safe’ alcohol intake practices, within national recommendations, during the postnatal period would remove any potential health risks to the infant from alcohol exposure at this vulnerable growth stage.